(untitled) (Psicologia USP, 2016)
This article intends to analyze the relations between trauma and sublimation based on the analysis of the testimonial, literary, poetic and autobiographical production of Primo Levi. Using Freud's proposition of distinction between the positive and negative effects of trauma as a starting point, the study of Primo Levi's work - including his interviews - shows that it is possible to sublimate from traumatic experiences, therefore articulating trauma and sublimation. At the same time, it is acknowledged that the scope of Primo Levi's sublimation during the decades were insufficient, stressing a hiatus that signalizes the return to the traumatic real. The work comes to an end with questionings about the role of psychoanalysis in the reading of human phenomena that go beyond the human capacity of significance.